Driving Firm Value: CSR, Abnormal Return, Trading Volume, and Profitability in Conventional Banking: Mengungkap Faktor-faktor Pendukung Nilai Perusahaan: Dampak CSR, Abnormal Return, Aktivitas Volume Perdagangan, dan Profitabilitas dalam Perbankan Konvensional - Muhammad Fadhil Mahdyanta; Wisnu P. Setiyono (Academia Open, 2022)
This study investigates the influence of Corporate Social Responsibility (CSR), Abnormal Return (AR), Trading Volume Activity (TVA), and Profitability on Firm Value in Conventional Banking Companies listed on the IDX for the 2015-2019 period. Employing purposive sampling, a sample of 13 pharmaceutical companies was selected. Secondary data was collected and analyzed using Eviews 10. The findings reveal that CSR, AR, TVA, and Profitability significantly affect Firm Value in Conventional Banking Companies. Additionally, the combined effect of these factors on Firm Value was observed. The implications of this study underscore the importance of incorporating CSR initiatives, managing abnormal returns, monitoring trading volume activity, and enhancing profitability to enhance firm value in the banking sector. These findings provide valuable insights for policymakers, practitioners, and scholars seeking to maximize firm value in the global banking industry. Highlights: Firm Value drivers: This study examines the impact of key factors, including CSR, abnormal return, trading volume activity, and profitability, on firm value in conventional banking companies listed on the IDX. Empirical evidence: The results indicate significant effects of CSR, abnormal return, trading volume activity, and profitability on firm value, providing valuable insights for maximizing firm value in the banking sector. Practical implications: Policymakers, practitioners, and scholars can utilize these findings to enhance firm value by incorporating CSR initiatives, managing abnormal returns, monitoring trading volume activity, and improving profitability in conventional banking. Keywords: Firm Value, CSR, Abnormal Return, Trading Volume Activity, Profitability